Comparison of 2-Dimensional, 3-Dimensional, and Surgical Measurements of the Tricuspid Annulus Size. (July 2015) - Dreyfus, Julien; Durand-Viel, Guillaume; Raffoul, Richard; Alkhoder, Soleiman; Hvass, Ulrik; Radu, Costin; Al-Attar, Nawwar; Ghodbhane, Walid; Attias, David; Nataf, Patrick; Vahanian, Alec; Messika-Zeitoun, David
<x xml:space="preserve">Abstract</x> Background— Associated tricuspid annuloplasty is recommended during left-heart valve surgery when the tricuspid annulus (TA) is dilated but methodology for the measurement of TA size and thresholds for TA enlargement are not clearly defined. Methods and Results— Measurement of the TA diameter (TAD) was prospectively performed using 2-dimensional transthoracic echocardiography (2D-TTE) in 282 patients in 4 different views (parasternal long axis, parasternal short axis, apical 4-chamber [A4C], and subcostal). TAD was also measured using 3D-transesophageal echocardiography in 183 patients (long axis), peroperatively in 120 patients who underwent a tricuspid valve surgery and using TTE (A4C) in 66 healthy volunteers. TAD was significantly different between the 4 2D-TTE views (3.85±0.58, 3.87±0.61, 4.02±0.69, and 3.92±0.65 cm, respectively; P<0.0001) but differences were small and the A4C was the most feasible (76%, 65%, 92%, and 73%, respectively; P<0.0001) and offered the highest reproducibility. TAD measured in A4C view was smaller than when measured by 3D-transesophageal echocardiography (3.90±0.63 versus 4.33±0.62 cm; P<0.0001) but correlation was excellent (r=0.84; P<0.0001) with a systematic 4-mm underestimation. In contrast, 2D-TTE measurements were significantly smaller and only modestly correlated to surgical measurements (4.11±0.61 versus 4.37±0.75 cm; P<0.0001; r=0.57; P<0.0001) which were poorly reproducible. In healthy volunteers, we suggested 42 mm or 23 mm/m2 as pathological values for the TAD in A4C. Conclusions— Measurements of the TAD using 2D-TTE in A4C were highly feasible and reproducible and despite being systematically smaller than 3D measurements, accurately reflected the degree of TA enlargement as assessed using 3D transesophageal echocardiography. We proposed the thresholds that may be used in future prospective studies to demonstrate whether a preventive strategy would improve the outcome.